G267 Preventing infection and mortality in down syndrome – the nottingham experience. (25th October 2020) - Prayle, AP; Shires, P; Baicher, V; Smith, S; Walton, L; McDermott, E; Marder, E
Abstract : Purpose: Children with Trisomy 21 are at increased risk of death compared to age-matched controls. We recently undertook a retrospective review of mortality in Trisomy 21 in our tertiary non-cardiac centre, and found an infective cause of death in 9/16 cases. Methods: In response to these data, we have undertaken a number of interventions at the Trust level with the goal of reducing the risk of future mortality and morbidity. New local guidance for preventing infection in Trisomy 21 Aggressively treating comorbidities such as reflux and sleep related breathing disorders Protocol driven assessment of immune function including functional antibodies and meticulous immunisation We recommend influenza and pneumovax II for all An alert on the Trust wide computer system for patients when they present in the emergency department or on the Children's Assessment Unit to emphasise the risk of infection in Trisomy 21 A review of how often and why children with Trisomy 21 present to ED Increasing awareness for parents, including an alert in the Down syndrome insert for the parent held child health record (the 'red book') A standardized alert sentence on all letters to primary care from the Trisomy 21 clinic emphasizing the risk of infection Increasing awareness amongst Clinicians, through programmed teaching, bulletins, and alerts Conclusions: We have instituted a series of measures to increase awareness of infection and sepsis in Trisomy 21, and to reduce the risk of serious bacterial infection. This is in direct response to local data on the causes of mortality in Trisomy 21 in our centre. Whilst it is too early to assess the results of the implemented measures, our experience shows that a multifaceted, multi-departmental approach to reducing risk of mortality can be implemented.